Cytomorphometric Changes in Hippocampal CA1 Neurons Exposed to Simulated Microgravity Using Rats as Model - Ranjan, Amit; Behari, Jitendra; Mallick, Birendra N. (Frontiers in Neurology, 2014)
Microgravity and sleep loss lead to cognitive and learning deficits. These behavioral alterations are likely to be associated with cytomorphological changes and loss of neurons. To understand the phenomenon, we exposed rats (225-275g) to 14 days simulated microgravity (SMg) and compared its effects on CA1 hippocampal neuronal plasticity, with that of normal cage control rats. We observed that the mean area, perimeter, synaptic cleft and length of active zone of CA1 hippocampal neurons significantly decreased while dendritic arborization and number of spines significantly increased in SMg group as compared with controls. The mean thickness of the post synaptic density and total dendritic length remained unaltered. The changes may be a compensatory effect induced by exposure to microgravity; however, the effects may be transient or permanent, which need further study. These findings may be useful for designing effective prevention for those, including the astronauts, exposed to microgravity. Further, subject to confirmation we propose that SMg exposure might be useful for recovery of stroke patients.